Performance Evaluation Model WRF for wind forecast in de central region of Alagoas State – Craíbas - Silva, Silvania Maria Santos da (2018)
The aim of this work was to evaluate the performance of the WRF model for estimate wind speed in the central region of Alagoas State (Brazil). The wind velocity (WRF outputs) were compared with anemometric data of the PVPN projetc (Previsão do Vento em Parques Eólicos no Nordeste Brasileiro “Wind forecast for wind farms in the Brazilian Northeast”), from January to December 2014. The results showed that the WRF model estimated very well the monthly and daily wind speed averages. Deviations are greater in the dry season. Throughout the year the mean difference (WRF-OBS) was only 0.23 m.s-1 (6.14 m.s-1 versus 5.91 m.s-1), showing that this model is a good tool for forecasting wind for wind farms.